Urine microbiome in individuals with an impaired immune system - Elsayed, Noha S.; Wolfe, Alan J.; Burk, Robert D. (Frontiers in Cellular and Infection Microbiology, 2024)
With the advent of next generation sequencing, it is now appreciated that human urine is not sterile. Recent investigations of the urinary microbiome (urobiome) have provided insights into several urological diseases. Urobiome dysbiosis, defined as non-optimal urine microbiome composition, has been observed in many disorders; however, it is not clear whether this dysbiosis is the cause of urinary tract disorders or a consequence. In addition, immunologically altered disorders are associated with higher rates of urinary tract infections. These disorders include immunoproliferative and immunodeficiency diseases, cancer, and immunosuppressant therapy in transplant recipients. In this review, we examine the current state of knowledge of the urobiome in immunologically altered diseases, its composition and metabolomic consequences. We conclude that more data are required to describe the urobiome in immune altered states, knowledge that could facilitate understanding the role of the urobiome and its pathophysiological effects on urinary tract infections and other disorders of the urinary tract.